Programa de ensino das habilidades manipulativas do badminton para adolescentes com síndrome de Down - Oliveira, Amália Rebouças de Paiva e (2016)
Down syndrome is a genetic alteration that results in some specific characteristics, for example, the delayed motor development and hypotonia. Stimulate motor skills of people with Down syndrome is very important to promote benefits such as autonomy, independence, resourcefulness and motor. Among the alternatives to provide this stimulus, this research worked with badminton, characterized as a racket sport responsible for stimulating the manipulative skills of its practitioners. This study aimed to analyze the effects of a badminton program in manipulative skills involved in this mode in adolescents with Down syndrome, and had the specific objective to describe the teaching strategies and learning resources used in badminton training for adolescents with Down syndrome and analyze the individual performance of each participant. Thus, a multiple baseline design was used to verify that the proposed activities of teaching influenced in learning the forehand skills; backhand; and serve. The teaching program was applied twice a week, lasting 30 minutes in which, each session consisted of three activities. The student took the 16 educational sessions to learn the proposed skills, and activities have been proven effective for teaching the forehand and backhand, however, the withdrawal of skill the student has achieved only 20% correct. Student B also needed 16 sessions and activities were effective for all three skills. In contrast, the pupil C, 18 needed teaching sessions, even though the student has taken longer to perform the forehand, the activities were effective for the three skills teaching. The elaborate badminton program highlighted some pedagogical resources that assisted learning of the participants, like balls of various sizes and different rackets. As teaching strategies include offering students the opportunity to choose the material to be used, demonstration, and the gradual removal by launching the shuttle for the hit. We conclude that the training program was effective to teach manipulative skills badminton students with Down syndrome, and teaching strategies and teaching resources facilitate the teaching - learning, thus making the sport accessible to the public concerned .